2019
DOI: 10.32479/irmm.7573
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Social Responsibility Disclosure in Terms of Quantity and Quality on the Financial Performance of Companies in Tunisia

Abstract: This article aims to study the relationship between the disclosure of corporate social responsibility (CSR) and the financial performance of Tunisian companies. Two measures are used to determine the CSR disclosure index: The first in terms of quantity is based on an unweighted approach from the Cooke (1991) study and the second in terms of quality is based on a system weighting of the qualitative characteristics of the information, referring to the voluntary declarations, in the annual reports of a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…CSR indices are developed using a number of different resources, including the Egyptian corporate governance code and existing literature (e.g. Patelli and Prencipe, 2007;Newson and Deegan, 2002;Rodrigues 2006 andKhan et al 2013;El-Halaby and Hussain 2016;Kalai & Sbais, 2019;Bucala, 2021 andVan Nguyen et al, 2022).…”
Section: Research Design 1-empirical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…CSR indices are developed using a number of different resources, including the Egyptian corporate governance code and existing literature (e.g. Patelli and Prencipe, 2007;Newson and Deegan, 2002;Rodrigues 2006 andKhan et al 2013;El-Halaby and Hussain 2016;Kalai & Sbais, 2019;Bucala, 2021 andVan Nguyen et al, 2022).…”
Section: Research Design 1-empirical Modelsmentioning
confidence: 99%
“…Content can be collected using a variety of content analysis techniques, such as word counts (e.g., Unerman 2000;and Guthrie et al, 2004) and classified indexes (e.g., Patelli and Prencipe, 2007;Chau and Grey, 2002) to identify key concepts. The CSR disclosure quantity index was used by Chakroun and Hussainey (2014), Alotaibi and Hussainey (2016), and Kalai & Sbais, (2019). It includes categories for disclosing information about environmental concerns, products and services, employees, community engagement, customers, governance and other relevant topics.…”
Section: Csr Quantity Indicesmentioning
confidence: 99%
“…Some of the earlier studies also examined the association between CSRD and company profitability. There was a positive connection between CSRD and company profitability (Alnajjar, 2000; Kalai and Sbais, 2019). In addition, other company characteristics such as use of social media and age of assets (Cormier et al , 2005) were shown to have a positive impact on disclosure.…”
Section: Corporate Social Responsibility Disclosure and Its Determinantsmentioning
confidence: 99%
“…Different stakeholders rely on corporate disclosures for different reasons in their decision-making process (Kalai & Sbais, 2019). They further described corporate social disclosures as a representation of the social responsibility of a particular business as presented and reported in their stand-alone reports or annual reports.…”
Section: Introductionmentioning
confidence: 99%
“…Different stakeholders sustained pressure on companies to release standalone or related reports. Studies have shown that social disclosure is positively associated with business value and efforts to determine the impacts of corporate social disclosures on the financial performance of companies have produced divergent results (Kalai & Sbais, 2019). Hence, the need to conduct a study on the effects of social disclosures on the financial performance of food and beverage manufacturers, specifically in Nigeria.…”
Section: Introductionmentioning
confidence: 99%